A Defined Combination of Four Active Principles From the Danhong Injection Is Necessary and Sufficient to Accelerate EPC-Mediated Vascular Repair and Local Angiogenesis - Shuang He; Shuang He; Hao Guo; Hao Guo; Tiechan Zhao; Tiechan Zhao; Yanzhi Meng; Yanzhi Meng; Rongrong Chen; Rongrong Chen; Jie Ren; Jie Ren; et al. (Frontiers Media S.A., 2019)
Many compounds in Chinese medicine formulae, including Danhong injection (DHI) formulae, are capable of stimulating angiogenesis and promoting vascular repair, but their chemical basis and action mechanisms remain poorly defined. The aim of this study is to determine the minimal native chemical composition of DHI for the pro-angiogenesis activity and to evaluate its contribution from local endothelial cells (ECs) and bone marrow-derived endothelial progenitor cells (EPCs). Our study demonstrated that the action of DHI in accelerating the recovery of hindlimb blood flow in a ischemic rat model was attributable to its local CXCR4-mediated pro-angiogenesis activity in mature endothelial cells, as well as to its ability to promote the proliferation, migration, adhesion, and angiogenesis of EPCs via integrated activation of SDF-1α/CXCR4, VEGF/KDR, and eNOS/MMP-9 signal pathways. Combination experiments narrowed down the angiogenic activity into a few components in DHI. Reconstitution experiment defined that a combination of tanshinol, protocatechuic aldehyde, salvianolic acid B, and salvianolic acid C in their native proportion was necessary and sufficient for DHI's angiogenic activity. Compared with the full DHI, the minimal reconstituted four active principles had the same effects in promoting tube formation in vitro, improving perfusion and recovery of ischemic limb, and enhancing angiogenesis in ischemic mice post-hindlimb ischemia in vivo.